Kesiapan Mental Atlet Atletik Kabupaten Banjarnegara Dalam Menghadapi Event Student Athletic Championship (SAC) Central Java - Feriska Amelia Putri; Donny Wira Yudha Kusuma; Ranu Baskora Aji Putra; Roas Irsyada (Universitas Negeri Semarang, 2024)
The Athletic Team in Banjarnegara Regency in facing the Central Java Students Athletic Championship (SAC) event has not been known the level of mental readiness because this is an international event that has only been held for the last two seasons. Mental Readiness is the most important thing in an athlete's performance in a match. Thus the purpose of this study is to determine the mental readiness of athletes in terms of motivation, self-confidence, anxiety and concentration. This study is a quantitative study with a survey design. The research analysis uses statistical analysis and descriptive exploration methods. The results of the analysis of the Mental Readiness of Athletic Athletes in Facing the Central Java Student Athletic Championship (SAC) Event are in the